World Military Expenditures and Arms Transfers, 1969-1978 ([Verlag nicht ermittelbar], 1984)
This two-part data collection contains annual information for military expenditures and import and export of arms and military equipment for 139 countries for the period 1969-1978. Data are provided on arms exports and imports, total imports and exports, arms imports and exports as a percentage of the total imports and exports, the gross national product (GNP), and central government expenditures, as well as expenditures on health, education, and the military as a percentage of the GNP, and health and education expenditures as a percentage of military expenditures. Data are also provided on population characteristics, such as the number of teachers, soldiers, and doctors per 1,000 people, the number of teachers and doctors as a percentage of the number of soldiers, and the total population. Other variables provide information on the country's membership in regional alliances such as the North Atlantic Treaty Organization, the former Warsaw Pact, and the Organization of Petroleum Exporting Countries, as well as World Bank membership. Additional variables describe the country's developmental status and the geographic region of the world in which the country is located. In addition, Part 1 data provide information on the total value of arms transferred from major arms supplier countries such as the United States, France, United Kingdom, Italy, Canada, Poland, China, and the Soviet Union, Czechoslovakia, and West Germany. They are organized by country records. Part 2 data are organized by country-year records.